A RARE CASE OF ANTIPHOSPHOLIPID SYNDROME PRESENTING AS ADRENAL CRISIS AND BILATERAL ADRENAL HEMORRHAGE - Goh, Qingci; Hamzah, Wan Mohd Hafez Wan; Mustafa, Norlaila; Wahab, Norasyikin (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Bilateral adrenal haemorrhage is a rare condition with potentially life-threatening consequences due to adrenal crisis. It can be the first presentation of antiphospholipid syndrome (APLS). We report a rare case of APLS presenting as an adrenal crisis and bilateral adrenal haemorrhage. CASE A 37-year-old male with a history of a motor vehicle accident 2 weeks ago presented with abdominal pain for 1 week, accompanied by nausea, vomiting, and lethargy. During the accident, where his motorbike skidded, he sustained an open fracture of the proximal phalanx of his little finger. Wound debridement was performed and a K-Wire was inserted. Clinical examination showed left-hand cellulitis, tenderness over the bilateral flank, and slightly low blood pressure (90/46 mmHg). Blood investigations revealed thrombocytopenia, hyponatremia, prolonged APTT that did not correct in the coagulation mixing study, and a low cortisol level (67 nmol/L). Abdominal CT scan revealed bilateral adrenal haemorrhage without any other solid organ and bowel injury. He was treated for acute adrenal crisis and subsequently started on hydrocortisone and fludrocortisone, resulting in significant clinical improvement. However, the left-hand cellulitis triggered digital artery thrombosis, leading to left-hand gangrene. Despite anticoagulation and ilioprost administration, he ended up with a left transradial amputation. Antiphospholipid syndrome was suspected in this patient based on the bilateral adrenal haemorrhage, digital artery thrombosis and abnormal coagulation profile. A full autoimmune work-up confirmed the presence of anticardiolipin, lupus anticoagulant, and anti-beta-2 glycoprotein. The anti-nuclear antibody was also positive 1:320, with a speckled pattern. C3, C4, anti-double stranded DNA and extractable nuclear antibodies were otherwise negative. He was discharged well on warfarin, hydrocortisone and fludrocortisone. CONCLUSION Adrenal insufficiency is a rare manifestation of APLS. This case highlights the importance of maintaining a high index of suspicion for APLS in patients presenting with bilateral adrenal haemorrhage and thrombotic events. Failure to diagnose or treat this condition promptly may lead to significant morbidity and mortality.